RAGAM ORCHIDACEAE EPIFIT DI KAWASAN UBALAN KEDIRI DAN PROSPEKNYA SEBAGAI MODAL BIOEKONOMI LOKAL - Amalia Sani Siamin Fitri; Agus Muji Santoso (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- This research was aimed to describe the kinds of Orchidaceae ephypitic in Ubalan Kediri. This research was conducted by describtive using explore method, started at Julii up to September 2013. Sampel were colected and to determine. Data shown that there were six specieses. They were Dendrobium crumenaatum  Swartz, Cymbidium biclolor (Lind.) Swartz, Rhynchostylis retusa  (Lind.) BI, Dendrobium secundum (BI.) Lind., Dendrobium anosmum Lind., dan Dendrobium tetrodon Ruhb.f. Based on karacters of flower analysis, both of R. retusa  (Lind.) BI andD. tetrodon  Ruhbf. have a greet capacities as local bioeconomy either conventionally or in vitro biotechnology. Keywords: Orchidaceae, Ubalan Kediri, Local Bioeconomy